IMPACT OF LIVESTOCK SECTOR FOR RURAL POVERTY ALLEVIATION IN CHITTOOR DISTRICT - Jalari, Vasu; Devarajulu, M. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Livestock sector plays avigorous role in socio-economic progress of rural families. Livestock rearing has substantial optimistic influence on equity in terms of employment, income and poverty lessening in rural zones by way of dispersal of livestock is more democratic as compared to land for agriculture purposes. In Andhra Pradesh, more than 5 percent of the rural households own livestock and a majority of livestock owning households are small, marginal and landless households. Small animals like sheep, goats, pigs and poultry are largely kept by the land scarce poor households for commercial purposes due to their low initial investment and operational costs. In the recent decade, demand for various livestock based products has increased considerably due to rise in per capita income, urbanization, taste and preference and increased awareness about food nutrition. Livestock sector is likely to arise as an appliance for agricultural progress in the coming years. This study only confined to Sree Rangaraja Puram Mandal in Chittoor District of Andhra Pradesh. In this paper author will make an attempt to analyses the performance of livestock sector in terms of livestock population, production, employment and income on one hand and the role of livestock sector in reducing rural poverty on the other. The study will also highlight the various major problems facing by the people those who are engaging in livestock sector in Sree Rangaraja Puram Mandal of Chittoor district.